ON THE EVOLUTION OF MIDDLE TRIASSIC PASSIVE MARGINS OF THE GREATER ADRIA PLATE: INFERENCES FROM THE STUDY OF CALC-ALKALINE AND SHOSHONITIC TUFFS FROM NW CROATIA - Slovenec, Damir; Horvat, Marija; Smirčić, Duje; Belak, Mirko; Badurina, Luka; Kukoč, Duje; Grgasović, Tonći; Byerly, Kevin; Vukovski, Matija; Šegvić, Branimir (Ofioliti, 2023)
Rhyolitic tuffs are readily found within the Northwestern Croatian Triassic Rift Basin which akems the southernmost segment of the geotectonic unit of the Southern Alps. The latter, located in the SW segment of the Zagorje-Mid-Transdanubian shear Zone, provides insights into the volcanism and geodynamic history of the passive margins of the Greater Adria Plate during the Middle Triassic. The eruptions at the time produced material that was distributed through air-fall transport and pyroclastic density currents, and after deposition gave rise to acidic pyroclastic rocks of the Pietra Verde type. These rocks are homogeneous to horizontally laminated, showing intervals of normal gradation and appear as vitroclastic, vitrocrystalloclastic, and crystalloclastic tuffs. Late Anisian-early Ladinian sub-alkaline, middle to high-K calc-alkaline, and shoshonitic tuffs feature a LREE over HREE enrichment, high LILE content, and HFSE depletion. Negative anomalies of the Nb-Ta pair, P, Sr, Eu, and Ti coupled with variable positive and negative spikes of Pb and Ba, respectively were also documented. An important contribution of the continental material in the evolution of the studied acidic rocks is attested by negative values of initial εNd (-2.7 to -4.95). Tuff petrogenesis essentially included melting of the heterogeneous lithospheric (subcontinental) mantle, subordinated melting of the continental crust and fractional crystallization of feldspar. Studied tuffs originated in a continental margin volcanic arc(?) environment formed during an active(?) northward subduction of the Paleotethyan lithosphere beneath the Eurasian Plate or, alternatively, more likely, during the passive continental rifting along the margins of the Greater Adria Plate.